Serum copper levels and risk of major adverse cardiovascular events: a systematic review and meta-analysis - Muñoz-Bravo, Carlos; Soler-Iborte, Eva; Lozano-Lorca, Macarena; Kouiti, Malak; González-Palacios Torres, Carla; Barrios-Rodríguez, Rocío; Jiménez-Moleón, José Juan (Frontiers in Cardiovascular Medicine, 2023)
Background Despite the fact that several studies have investigated the association between serum copper levels (S-Cu) and the risk of cardiovascular diseases, this relationship remains unclear. The aims of this study were to investigate the association between S-Cu and risk of major adverse cardiovascular events (MACE), including total stroke, ischemic stroke, hemorrhagic stroke, myocardial infarction and cardiovascular mortality, and identify potential sources of results heterogeneity. Methods We carried out a systematic review and meta-analysis. The selection criteria were: (1) Observational studies (cohort studies, case-control studies and hybrid studies); (2) Studies containing quantitative data about the relationship between S-Cu and risk of MACE; (3) Estimating association measures; and (4) Studies written in English, French or Spanish. Overall pooled Odds ratio (pOR) and 95% confidence intervals (95% CI) of MACE for the highest vs. lowest S-Cu category were calculated using random-effects models. Results Sixteen studies with a total of 41,322 participants were included in the meta-analysis: 10 prospective cohort studies, 5 nested case-control studies and 1 case-control study. Comparing highest vs. lowest category, high S-Cu levels were associated with total stroke (pOR: 1.49, 95% CI 1.22–1.82; I2 = 0%, p = 0.54), myocardial infarction (pOR: 1.31, 95% CI 1.17–1.46; I2 = 0.0%, p = 0.92) and cardiovascular mortality (pOR: 1.60, 95% CI 1.39–1.86; I2 = 0.0%, p = 0.54). Subgroup analysis showed that studies with a hybrid design had higher risks for cardiovascular mortality (pOR: 3.42, 95% CI 1.98–5.92) and ischemic stroke (pOR: 1.54, 95% CI 1.30–1.83). Conclusion High S-Cu levels were associated with an increased risk of total stroke, myocardial infarction and cardiovascular mortality. Hybrid studies seems to modify the strength of the association between S-Cu and the risk of cardiovascular mortality and ischemic stroke. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022370782], identifier [CRD42022370782].